ACE I/D genotype in professional field hockey players - Gronek, P.; Holdys, J.; Konarski, J.; Krysciak, J.; Wolc, A. (Trends in Sport Sciences, 2013)
Numerous studies have focused on the association between I/D ACE and physical fitness; however, this association in professional hockey players has never been recognized. Aim of the Study. The study examined the distribution of Alu insertion (I)/deletion (D) angiotensin converting enzyme (ACE) genotypes in elite male professional field hockey players. Material and Methods. The effect of Alu insertion (I)/deletion (D) angiotensin converting enzyme (ACE) genotypes on motor skills and maximal oxygen uptake (VO2max) in 47 elite male field hockey players was studied. Genotyping for ACE I/D was performed using a polymerase chain reaction on DNA from leucocytes. The studied motor skills such as speed - 20 m run, power - vertical jump, recovery - step-test, speed endurance (15 x 20 m) shuttle run, were established using functional tests. The VO2max was measured during progressive exercise test till exhaustion. Results. The authors do not confirm some literature data that D allele favours endurance ability. We did not detect significant genotype effects of ACE on the analyzed traits; however a tendency for decreased performance of individuals with the DD genotype was noted for vertical jump, power peak and power. Conclusions. Analysis of the genetic profile of ACE I/D may provide supplemetary information on a player`s predispositions to exercise with specific energy requirements.